Biologic and synthetic skin substitutes: An overview - Ahmad Sukari Halim; Teng Lye Khoo; Shah Jumaat Mohd. Yussof (Indian Journal of Plastic Surgery)
The current trend of burn wound care has shifted to more holistic approach of improvement in the long-term form and function of the healed burn wounds and quality of life. This has demanded the emergence of various skin substitutes in the management of acute burn injury as well as post burn reconstructions. Skin substitutes have important roles in the treatment of deep dermal and full thickness wounds of various aetiologies. At present, there is no ideal substitute in the market. Skin substitutes can be divided into two main classes, namely, biological and synthetic substitutes. The biological skin substitutes have a more intact extracellular matrix structure, while the synthetic skin substitutes can be synthesised on demand and can be modulated for specific purposes. Each class has its advantages and disadvantages. The biological skin substitutes may allow the construction of a more natural new dermis and allow excellent re-epithelialisation characteristics due to the presence of a basement membrane. Synthetic skin substitutes demonstrate the advantages of increase control over scaffold composition. The ultimate goal is to achieve an ideal skin substitute that provides an effective and scar-free wound healing.